Rural Minority Student Engagement with a Healthcare Pipeline Program - Karri A. Holley (Journal of Research in Rural Education, 2013)
Rural communities are underserved by the medical profession. This shortage is particularly acute for minority rural communities lacking reliable access to minority healthcare professionals. This article reports the results of a study designed to understand the attitudes and responses of rural minority students who participated in a program designed to increase the number of rural physicians. Data were collected through interviews with students and program faculty as well as classroom observations and document analysis. Findings emphasized the importance of recognizing the needs of rural areas, networking between peers and rural professionals, understanding the steps required for receiving a medical degree, and acknowledging students' cultural capital related to rural communities. The article concludes with recommendations for educators focused on underrepresented student populations or specific community needs.